2008
DOI: 10.1111/j.1365-2990.2007.00910.x
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐smooth muscle actin (α‐SMA) and nestin expression in reactive astrocytes in multiple sclerosis lesions: potential regulatory role of transforming growth factor‐beta 1 (TGF‐β1)

Abstract: Reactive astrocytes in active MS lesions re-express alpha-SMA and nestin. We suggest that the in vivo re-expression might be under regulation of TGF-beta1. These results further clarify the regulation of astrocyte activity after CNS injury, which is important for the astroglial adaptation to pathological situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
39
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 57 publications
8
39
0
1
Order By: Relevance
“…Scale bar 50 µm. (Color figure online) MS. Then, our observations are in agreement with the data related by Morrels et al [27]. Balo's concentric MS can lead to death but magnetic resonance imaging reveals that lesions can decrease in size and do not progress in some patients.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Scale bar 50 µm. (Color figure online) MS. Then, our observations are in agreement with the data related by Morrels et al [27]. Balo's concentric MS can lead to death but magnetic resonance imaging reveals that lesions can decrease in size and do not progress in some patients.…”
Section: Discussionsupporting
confidence: 95%
“…However, concerning pathological conditions affecting the CNS, one study reports the expression of α-SM actin by astrocytes in multiple sclerosis (MS) [27]. Indeed, Morrels et al [27] indicates that this subpopulation of astrocytes co-expressing GFAP and α-SM actin was observed in active or acute MS lesions. The authors did not find this astrocyte subpopulation in MS chronic inactive situations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We demonstrated that elongated, astrocytic processes after trauma played a crucial role in cell migration (Fig. 4 A-E), and intriguingly, similar elongated processes in reactive astrocytes are observed in multiple sclerosis (54). Because we observed neurites from transplanted cells in the cochlear nucleus, surface transplantation may be applied not only to neural systems in the superficial layers of the nervous system but also to those in deeper locations.…”
Section: Discussionmentioning
confidence: 76%
“…However, a significant upregulation of nestin is observed after cerebral injury suggesting that nestin is involved in brain repair (Frisen et al, 1995, Holmin et al, 1997, Douen et al, 2004). There is abundant evidence in the literature that after brain injury nestin expression in mature brains is a marker of reactive astrocytes (Clarke et al, 1994, Lin et al, 1995, Duggal et al, 1997, Holmin et al, 1997, Wei et al, 2002, Douen et al, 2004, Moreels et al, 2008). The lack of nestin expression, in our conditions, in the absence of DFP is shown in supplementary data.…”
Section: Discussionmentioning
confidence: 99%